Molecular cloning, sequencing and sequence analysis of Thermus thermophilus tyrosyl-tRNA synthetase - Yaremchuk, A.D.; Kovalenko, O.P.; Gudzera, О.I.; Tukalo, M.A. (Біополімери і клітина, 2004)
The gene encoding tyrosyl-tRNA synthetase (TyrRS) from the extreme thermophilic eubacterium T. thermophilus HB27 has been cloned and sequenced. The open reading frame encodes a polypeptide chain of 432 amino acid residues in length (molecular mass 48717 Da). Comparison of the amino acid sequence of the T. thermophilus TyrRS (TyrRSTT) with those of TyrRS from various organisms shows that T. thermophilus enzyme shares a branch in the philogenetic tree of eubacterial TyrRSs with the enzymes from Aquifex aeolicus, Deinococcus radiodurans, Haemophilus influenzae and Helicobacter pyroly (40-57 % amino acid identity), distinct from the branch containing Esherichia coli, Chlamydia trachomatis and Bacillus stearothermophilus, for example (24–28 % amino acid identity). The TyrRS active site domain is highly conserved, whereas a C-terminal tRNA binding domain contains only few conserved residues. But even in the active site exists one very important difference between the two groups of bacterial TyrRSs: Lys-41 in TyrRSTT (and in TyrRS from many human pathogenic bacteria) is conserved as a tyrosine in another group of bacterial TyrRSs and eukaryotic sequences including human. This knowledge could be exploited in the design of new antibiotics. Клоновано та визначено нуклеотидну послідовність гена, що кодує тирозил-тРНК синтетазу (TyrRS) із екстремальнотермофільної еубактеріХ Т. thermophilus НВ27 (TyrRSTT). Відкрита рамка зчитування кодує поліпептидний ланцюг довжиною 432 амінокислотних залишки (молекулярна маса 48717 Да). Порівняння амінокислотної послідовності TyrRSTT з відповідними послідовностями інших організмів виявило, що фермент із Т. thermophilus належить до тієї ж гілки філогенетичного дерева еубактеріальних TyrRS, що й ферменти із Aquifex aeolicus, Deinococcus radiodurans, Haemophilus influenzae і Helicobacter pyroly (ідентичність 40–57 %), але не до тієї, до якої належать, наприклад, Escherichia coli, Chlamydia trachomatis і Bacillus stearothermophilus (24–28 % ідентичності). Амінокислотна послідовність каталітичного домену висококонсервативна, тоді як тРНК-зв'язувальний С-кінцевий домен містить лише невелику кількість консервативних залишків. Але навіть в активному центрі існує важлива відмінність між двома групами еубактеріальних TyrRS: залишок Lys-41 в TyrRSTT (і в TyrRS із багатьох патогенних бактерій людини) представлений консервативним залишком тирозину в бактеріальних TyrRS іншої групи, а також еукаріотичних TyrRS, включаючи людину. Ця відмінність може бути використана при створенні нових антибіотиків. Клонирован ген, кодирующий тирозил-тРНК синтетазу (TyrRS) из экстремально термофильной эубактерии Т. thermophilus НВ27 (TyrRSTT), и определена его нуклеотидная последовательность. Открытая рамка считывания кодирует полипептидную цепь длиной 432 аминокислотных остатка (молекулярная масса 448717 Да). Сравнение аминокислотных последовательностей TyrRSTT с соответствующими последвательностями из других организмов выявило, что фермент из Т. thermophilus относится к той же ветви филогенетического древа эубактериальных TyrRS, что и ферменты из Aquifex aeolicus, Deinococcus radiodurans, Haemophilus influenzae и Helicobacter pyroly (идентичность 40–57 %), но не к той, к которой принадлежат, например, Escherichia coli, Chlamydia trachomatis и Bacillus stearothermophilus (24–28 % идентичности). Аминокислотная последовательность каталитического домена высококонсервативна, в то время как тРНК-связывающий С-концевой домен содержит лишь несколько консервативных остатков. Однако даже в последовательности активного центра отмечено важное различие между двумя группами эубактериальных TyrRS: остаток Lys-41 в TyrRSTT (и в TyrRS из многих патогенных бактерий человека) представлен консервативным остатком тирозина в бактериальных TyrRS другой группы, а также в TyrRS эукариот, включая человека Это отличие может быть использовано при создании новых антибиотиков.